Workshop Pembelajaran Kooperatif (Jigsaw, Number Head Together, Make A Match, dan Two Stay Two Stray) bagi Guru-guru Sekolah Dasar KKG III Rasau Jaya, Kabupaten Kubu Raya - Suparjan Suparjan (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2020)
The results of preliminary observations and interviews concluded that teachers at the Primary School Teacher Working Group (KKG) III in Rasau Jaya Village, Kubu Raya Regency, West Kalimantan, needed a new method and innovation in learning activities. So a workshop was held with the aim of increasing the knowledge, understanding, and abilities of teachers in cooperative learning procedures, especially designing and implementing the jigsaw learning model, number head together, make a match, and two stay two stray. The workshop was held in four stages: (1) planning, (2) implementation, (3) mentoring, and (4) evaluation. The output showed that the workshop increased the knowledge, understanding and ability of teachers in designing and implementing cooperative learning, especially the Jigsaw learning model, Number Head Together, Make A Match, and Two Stay Two Stray.